G460(P) Clinical phenotype of children and young people with renal dysplasia in scotland. (24th May 2017) - Dalrymple, RA; Maxwell, H; Gardiner, C
Abstract : Aims: To describe the clinical and genetic phenotype of children and young people known to the Scottish Paediatric Renal and Urology Network with a diagnosis of renal dysplasia. Introduction: Single gene disorders are increasingly being identified as the underlying cause of renal dysplasia. A detailed clinical phenotype can guide which genetic mutations to test for and a positive genetic diagnosis has been shown to be useful for patients, families and clinicians. Methods: This was an observational study looking at the clinical records of all children and young people with renal dysplasia in Scotland. The Strathclyde electronic renal patient record system (SERPR) was searched for patients aged 25 years or under with a diagnosis of 'renal dysplasia/hypoplasia/hypodysplasia' or 'renal cysts with diabetes syndrome'. The diagnosis of renal hypodysplasia was confirmed by review of radiological, biochemical and pathological investigations. Patients with obstructive uropathy and neuropathic bladder were excluded, as were patients with acquired renal scarring. The coding system, clinical letters and pathology results were searched for information about their clinical phenotype and severity of renal disease. Results: To date there are 180 children and young people identified with a diagnosis of renal dysplasia. 41 patients are known to have a definite diagnosis, including 15 patients with a HNF1B mutation which is the commonest genetic cause of renal dysplasia. 20 patients have other known syndromes including brachiooto renal syndrome and townes brock syndrome and 6 have chromosomal abnormalities. A further 36 children have features suggestive of a genetics diagnosis and are currently under investigation. Conclusion: In this cohort of Scottish children with renal dysplasia there is a high incidence of genetic and syndromic diagnoses. More children would benefit from genetics input and testing which we are planning for this cohort.